Pemanfaatan Rumput Laut Eucheuma Spinosum dan Halimeda Sp., sebagai Perangkap dalam Penangkapan Ikan Baronang Menggunakan Bubu di Perairan Pantai Kartini Jepara - Izzati, Munifatul (BULETIN ANATOMI DAN FISIOLOGI dh SELLULA, 2009)
We investigated the use of Eucheuma spinosum and Halimeda sp as a trap for the Rabbitfish, Syganus sp. The aim of this research is to maximize the yield of Syganid by fisherman. Result s indicated that using seaweeds as a trap, 45% of harvested fish was dominated by Syganus sp. The presence of seaweeds lead toaccumulation of Syganid. In using combination of seaweeds, i.e: Eucheuma spinosum + Halimeda sp at the distance of 10cm give the highest yield of fish. To maximize the traps, we have to also consider in using other technique such as arrangement of trap position and hole size of the traps.